Design of a pressure sensor based on optical fiber Bragg grating lateral deformation - Urban, Frantisek; Kadlec, Jaroslav; Vlach, Radek; Kuchta, Radek (Sensors (Basel, Switzerland), 2010)
This paper describes steps involved in the design and realization of a new type of pressure sensor based on the optical fiber Bragg grating. A traditional pressure sensor has very limited usage in heavy industrial environments, particularly in explosive or electromagnetically noisy environments. Utilization of optics in these environments eliminates all surrounding influences. An initial motivation for our development was the research, experimental validation, and realization of a complex smart pressure sensor based on the optical principle. The main benefit of this solution consists of increasing sensitivity, resistance to electromagnetic interference, dimensions, and potential increased accuracy.
Keywords: technologie optických vláken; optika a fotonika; Equipment Design; biologické modely; teoretické modely; fiber Bragg grating; Optical Fibers; počítačová simulace; Optics and Photonics; fiber optic; Fiber Optic Technology; Finite Element Analysis; Elasticity; pressure sensor; pružnost; tlak; Models, Biological; Electromagnetic Fields; Torsion, Mechanical; Computer Simulation; torze mechanická; biomechanika; optická vlákna; elektromagnetická pole; analýza metodou konečných prvků; design vybavení; Models, Theoretical; Biomechanical Phenomena; Pressure